The Impact of a School-Based Intervention Using the PBSEIM Model on Health Promoting Behaviors and Self-Care in Adolescent Females - Fahimi Rad, Elahe; Keshavarz, Zohreh; Simbar, Masoumeh; Nasiri, Malihe; Mehraliyan, Hasan (Advances in Nursing & Midwifery, 2017)
Abstract Introduction: Developing effective health habits during adolescence dramatically effects behavior formation during adulthood. Therefore, the current study was conducted with an aim to investigate the impact of school-based intervention using «Integrated Model of Planned Behavior and Self-Efficacy» (PBSEIM) on self-care and health promoting behaviors of female high school students of Abyek city, Qazvin Province (Iran), during year 2016. Methods: This experimental study was conducted on 100 female public high school students aged 15 to 19 years old in Abyek city, Qazvin Province. Two schools were randomly selected between 6 high schools. One of the high schools was randomly selected as the intervention group and the other one as the control group. Three classrooms in each school were randomly selected and the necessary samples were collected from each class. Overall, 100 samples had the inclusion criteria; 50 were included in the intervention and 50 in the control group. Demographic, “Health Promoting Lifestyle Profile” (HPLP II), and “Adolescent Girl’s Self-Care Questionnaire” was completed by both groups before and after the interventions. Face validity and content validity of the self-care questionnaire were assessed. Also, Cronbach’s alpha coefficient for this questionnaire was obtained as 0.73.The students in the intervention group were trained using the PBSEIM model and the control group received routine training. Data was collected and analyzed using the SPSS software (version 22) and independent and paired t tests. Values lower than 0.05 were considered significant. Results: There was a significant difference before and after the intervention in the average scores of health-promoting behaviors and self-care of adolescents in the intervention group in comparison to the control group (P < 0.05). Inter-group comparison demonstrated a significantly higher increase of health-promoting behaviors and self-care of adolescents in the intervention group before and after the intervention (P-value < 0.05). Conclusions: School-based educational intervention using psychosocial models is effective in changing health-promoting behaviors and self-care.